The floral transcriptome of Eucalyptus grandis. Issue 4 (29th October 2014) - Vining, Kelly J.; Romanel, Elisson; Jones, Rebecca C.; Klocko, Amy; Alves‐Ferreira, Marcio; Hefer, Charles A.; Amarasinghe, Vindhya; Dharmawardhana, Palitha; Naithani, Sushma; Ranik, Martin; Wesley‐Smith, James; Solomon, Luke; et al.
Summary: As a step toward functional annotation of genes required for floral initiation and development within the Eucalyptus genome, we used short read sequencing to analyze transcriptomes of floral buds from early and late developmental stages, and compared these with transcriptomes of diverse vegetative tissues, including leaves, roots, and stems. A subset of 4807 genes (13% of protein‐coding genes) were differentially expressed between floral buds of either stage and vegetative tissues. A similar proportion of genes were differentially expressed among all tissues. A total of 479 genes were differentially expressed between early and late stages of floral development. Gene function enrichment identified 158 gene ontology classes that were overrepresented in floral tissues, including 'pollen development' and 'aromatic compound biosynthetic process'. At least 40 floral‐dominant genes lacked functional annotations and thus may be novel floral transcripts. We analyzed several genes and gene families in depth, including 49 putative biomarkers of floral development, the MADS‐box transcription factors, 'S‐domain'‐receptor‐like kinases, and selected gene family members with phosphatidylethanolamine‐binding protein domains. Expanded MADS‐box gene subfamilies in Eucalyptus grandis included SUPPRESSOR OF OVEREXPRESSION OF CO 1 ( SOC1 ), SEPALLATA ( SEP ) and SHORT VEGETATIVE PHASE ( SVP ) Arabidopsis thaliana homologs. These data provide a rich resource for functional and evolutionary analysis of genes controlling eucalypt floral development, and new tools for breeding and biotechnology. Abstract : Featured paper: see also the Commentary by Strauss & Myburg